Posterior cranial vault distraction osteogenesis: A systematic review - Sameer Pandey; Gosla S. Reddy; Ashi Chug; Ashutosh Dixit (Elsevier, 2022)
Purpose: Posterior cranial vault distraction osteogenesis (PCVDO) has become the treatment of choice in specific indications within 12 years since its introduction in 2009. It is used to treat or prevent Intracranial hypertension secondary to craniosynostosis. However, there is still a lack of evidence describing this procedure's safety concerning the osteotomy line being close to the torcula. This systematic review aims to generate evidence regarding the safety of this new technique. Materials and method: A systematic search of Pubmed and Embase database were done without any time limit until the last search date of July 31, 2021. Articles focused on posterior cranial vault distraction osteogenesis were shortlisted using defined inclusion criteria. In addition, complications, volume gain, and distraction protocols in patients with craniosynostosis were assessed. Results: The review included 11 articles from 11 different centres. Of the Total 241 patients, 51 were non-syndromic patients, and 190 were syndromic patients. There were 242 procedures done on 241 patients. The proportion of patients with complications was 30%. Wound infection was the most commonly reported complication. PCVDO resulted in 20-25% volume gain and successfully prevented increased intracranial pressure (ICP). Conclusion: The systematic review has significantly identified a 30.606% incidence of complications in PCVDO. No mortality was linked directly to the Posterior cranial vault distraction osteogenesis procedure (PCVDO). The authors identified the evolution of many unique vectors and osteotomy designs customized for patients and practices for safe surgery. The effects of PCVDO on the anterior cranial fossa remain a topic of interest and require observational studies for better understanding.